Influence of a new fishpond design on invertebrate community biodiversity and secondary production - Roucaute Marc; Aubin Joël; Nahon Sarah; Jaeger Christophe (Aquatic Living Resources, 2024)
The aim of this study was to compare the impact of three aquaculture production systems on the biodiversity and productivity of aquatic invertebrates. We compared two conventional fishpond designs (extensive and semi-intensive) with a new design combining a semi-intensive carp polyculture fishpond with a planted lagoon, called coupled semi-intensive design. All fishponds were stocked with the same proportions of common carp, roach, and Eurasian perch. Fish density was double in coupled semi-intensive and semi-intensive ponds compared to extensive ponds for which no formulated feed was provided. Benthic macroinvertebrates were sampled in May and September. Zooplankton was sampled monthly from May to November. For benthic macroinvertebrates, community taxonomic richness, biomass, production, and mean individual dry mass were higher in lagoons than in the coupled semi-intensive, semi-intensive and extensive fishponds. Zooplankton production was highest in extensive fishponds and lowest in coupled semi-intensive ponds. Zooplankton production peaked in summer and was lower than benthic macroinvertebrates production in May and September. Asellus aquaticus, whose production was higher in September than May, was the dominant macroinvertebrate in lagoons, but was almost absent from all fishponds. Bosmina longirostris, the most productive plankton taxon, especially in extensive fishponds, reached peak production in July and August. Our study highlighted the functional role of a shallow, fishless, planted lagoon linked to the fishpond for biodiversity and production of benthic macroinvertebrates and zooplankton.